When right makes might : rising powers and world order - Goddard, Stacie E., 1974- (Cornell studies in security affairs., 2018)
"Analyzes the question of whether great powers choose to accommodate, contain, or confront a rising power depends on the legitimacy of the challenger's expansionist aims"--